2011
DOI: 10.4049/jimmunol.1100382
|View full text |Cite
|
Sign up to set email alerts
|

Y-Box Binding Protein-1 Mediates Profibrotic Effects of Calcineurin Inhibitors in the Kidney

Abstract: The immunosuppressive calcineurin inhibitors (CNIs) cyclosporine A (CsA) and tacrolimus are widely used in transplant organ recipients, but in the kidney allograft, they may cause tubulointerstitial as well as mesangial fibrosis, with TGF-β believed to be a central inductor. In this study, we report that the cold-shock protein Y-box binding protein-1 (YB-1) is a TGF-β independent downstream effector in CsA- as well as in tacrolimus- but not in rapamycin-mediated activation of rat mesangial cells (rMCs). Intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Prior to immunoprecipitation, polyclonal anti-YB-1 Ab and irrelevant antirabbit IgG (Cell Signaling) as negative control were covalently linked to protein A-Sepharose beads (50% suspension; Invitrogen), as described before (23). A total of 20 ml protein A-Sepharose coupled either with polyclonal anti-YB-1 Ab or nonspecific IgG incubated with 200 mg kidney cell extract from LPS-stimulated or control-untreated recombinant mesangial cells for 1.5 h at 4˚C in immunoprecipitation buffer (20 mM HEPES [pH 7.4], 100 mM potassium chloride, 5 mM magnesium acetate, 1 mM DTT, 0.025% Triton X-100, and protease inhibitors).…”
Section: Coimmunoprecipitation Of Mrna Associated With Yb-1mentioning
confidence: 99%
“…Prior to immunoprecipitation, polyclonal anti-YB-1 Ab and irrelevant antirabbit IgG (Cell Signaling) as negative control were covalently linked to protein A-Sepharose beads (50% suspension; Invitrogen), as described before (23). A total of 20 ml protein A-Sepharose coupled either with polyclonal anti-YB-1 Ab or nonspecific IgG incubated with 200 mg kidney cell extract from LPS-stimulated or control-untreated recombinant mesangial cells for 1.5 h at 4˚C in immunoprecipitation buffer (20 mM HEPES [pH 7.4], 100 mM potassium chloride, 5 mM magnesium acetate, 1 mM DTT, 0.025% Triton X-100, and protease inhibitors).…”
Section: Coimmunoprecipitation Of Mrna Associated With Yb-1mentioning
confidence: 99%
“…CsA and FK506 both inhibit calcineurin, which is responsible for calcium-dependent signal transduction, thereby preventing the transcription of lymphokine genes, such as interleukin-2, and inhibiting T-cell activation and proliferation [32]. However, a fibrogenic effect of CsA and FK506 has been described earlier in renal allografts and in animal and in vitro models [19][20][21]. The fibrogenic effects are predominantly mediated by elevated expression of transforming growth factor-b, suppressed matrix metalloproteinase activity and augmented fibroblast collagen synthesis [20,21].…”
Section: Bronchiolitis | Ke Hostettler Et Almentioning
confidence: 94%
“…The fibrogenic effects of CsA and FK506 have been studied extensively in renal allografts [19], and are predominantly mediated by elevated expression of transforming growth factor-b [20,21]. In addition, previous data have demonstrated that CsA may directly stimulate cell proliferation [22,23], raising the possibility that calcineurin inhibitors may contribute to the development of chronic GvHD in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…The Ybx1 is a key regulator of cell growth, apoptosis, drug resistance, DNA repair and transcription. It has been shown that overexpression of Ybx1 via Erk/Akt pathway can monitor damage recognition and renal fibrosis of toxic agents such as Cyclosporine [48][49][50]. However, the role of Pcgf4 and Ybx1 in nephrotoxicity has not yet been fully evaluated.…”
Section: Discussionmentioning
confidence: 99%